KEPEMIMPINAN TRANSFORMASIONAL DALAM MENINGKATKAN KINERJA GURU DI SEKOLAH DASAR - Dessy Ismaya Firmani; Idis Suherlan; Miranty Nurhayati; Yulia Rusmiati; Dinny Mardiana (STKIP Subang, 2026)
This study aims to describe the role of principals' transformational leadership in improving teacher performance in elementary schools. Transformational leadership is considered an effective leadership approach that promotes positive change through motivation, inspiration, individual consideration, and teachers’ professional development. This research employed a qualitative approach using a descriptive method. Data were collected through observations, interviews, and documentation involving principals and teachers in elementary schools. Data analysis was conducted through data reduction, data display, and conclusion drawing. The findings indicate that principals' transformational leadership has a positive impact on improving teacher performance, as reflected in increased work discipline, creativity in teaching and learning processes, classroom management skills, collaboration among teachers, and commitment to enhancing educational quality. Principals play significant roles as motivators, innovators, and role models in creating a conducive school culture oriented toward improving the quality of learning. Supporting factors in the implementation of transformational leadership include effective communication, a supportive school environment, and active teacher participation, while the challenges identified include limited facilities and infrastructure as well as differences in teachers’ characteristics. Therefore, transformational leadership can serve as an effective strategy for improving teacher performance in elementary schools to achieve better educational quality.